Time spent at a high percentage of VO2max for short intermittent runs: active versus passive recovery - Dupont, G.; Berthoin, S. (Canadian Journal of Applied Physiology, 2004)
The purpose of this study was to compare the effects of recovery type (active vs. passive) on the time spent at VO(2)max and above 90 % of VO(2)max during short intermittent runs (15 s) at 120 % of maximal aerobic speed. Twelve male subjects performed a graded test and intermittent runs (15 s) alternated with 15 s of active recovery (50 % of maximal aerobic speed) or with 15 s of passive recovery to exhaustion. The time to exhaustion during the intermittent runs with active recovery (445 +/- 79 s) was significantly shorter (p < 0.001) compared with passive recovery (745 +/- 171 s). No significant difference was found between time spent at VO(2)max and above 90 % of VO(2)max for intermittent runs alternated with active recovery (180 +/- 121 s and 282 +/- 117 s, respectively ) and intermittent runs alternated with passive recovery (191 +/- 135 s and 317 +/- 132 s, respectively ). The times spent at VO(2)max (p < 0.05) and above 90 % of VO(2)max (p < 0.001), expressed in percentage of time to exhaustion, were significantly longer for intermittent runs alternated with active recovery (41 +/- 27 % and 64 +/- 24 %, respectively) than with passive recovery (25 +/- 16 % and 43 +/- 16%, respectively). In conclusion, the present study has shown that the time to exhaustion during repeated high-intensity exercise was significantly greater for passive compared with active recovery, despite no difference in absolute time spent at a high percentage of VO(2)max. However, the time spent at a high percentage of VO(2)max, expressed as a percentage of time to exhaustion, was significantly higher for active compared with passive recovery.